Mexico : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The IMF staff report on Mexico's financial policies has been satisfactory; these policies have been said to act as a buffer against risks that erupted during the global economic crisis. Mexico has been identified as a prudent and fairly well-managed economy. However, the issues that would pose a challenge to the financial sector and would hamper overall economic stability of the country were emphasized, and certain key areas that need attention on a priority basis were highlighted.